Biosynthesis and incorporation of an alkylproline-derivative (APD) precursor into complex natural products - Janata, J; Kamenik, Z; Gazak, R; Kadlcik, S; Najmanova, L (Natural product reports, 2018)
Covering: up to 2017This review covers the biosynthetic and evolutionary aspects of lincosamide antibiotics, antitumour pyrrolobenzodiazepines (PBDs) and the quorum-sensing molecule hormaomycin. These structurally and functionally diverse groups of complex natural products all incorporate rarely occurring 4-alkyl-l-proline derivatives (APDs) biosynthesized from l-tyrosine through an unusual specialized pathway catalysed by a common set of six proteins named Apd1-Apd6. We give an overview of APD formation, which involves unusual enzyme activities, and its incorporation, which is based either on nonribosomal peptide synthetase (PBDs, hormaomycin) or a unique hybrid ergothioneine-dependent condensation system followed by mycothiol-dependent sulphur atom incorporation (lincosamides). Furthermore, within the public databases, we identified 36 novel unannotated biosynthetic gene clusters that putatively encode the biosynthesis of APD compounds. Their products presumably include novel PBDs, but also novel classes of APD compounds, indicating an unprecedented potential for the diversity enhancement of these functionally versatile complex metabolites. In addition, phylogenetic analysis of known and novel gene clusters for the biosynthesis of APD compounds allowed us to infer novel evolutionary hypotheses: Apd3 methyltransferase originates from a duplication event in a hormaomycin biosynthetic gene cluster ancestor, while putative Apd5 isomerase is evolutionarily linked to PhzF protein from the biosynthesis of phenazines. Lastly, we summarize the achievements in preparing hybrid APD compounds by directing their biosynthesis, and we propose that the number of nature-like APD compounds could by multiplied by replacing l-proline residues in various groups of complex metabolites with APD, i.e. by imitating the natural process that occurs with lincosamides and PBDs, in which the replacement of l-proline for APD has proved to be an evolutionary successful concept.
Keywords: benzodiazepiny; molekulární evoluce; glykopeptidy; biologické přípravky; Cysteine; Anti-Bacterial Agents; ergothionein; linkosamidy; linkomycin; Depsipeptides; inositol; cystein; Inositol; Antineoplastic Agents; Lincomycin; protinádorové látky; Humans; Benzodiazepines; antibakteriální látky; molekulární struktura; depsipeptidy; Lincosamides; Ergothioneine; Biological Products; Glycopeptides; lidé; Molecular Structure; Evolution, Molecular